Sensory pollutants have negative but different effects on nestbox occupancy and breeding performance of a nocturnal raptor across Europe - Orlando, Giuseppe; Nelli, Luca; Baker, Paul; Karell, Patrik; Vrezec, Al; Treinys, Rimgaudas; Bucciolini, Gian Luigi; Poprach, Karel; Anderson, David; Anderson, Katy; Baudvin, Hugues; Olivier, Gérard; et al. (Biological Conservation, 2026)
Anthropogenic noise and artificial light at night (ALAN) are expanding globally, acting as pervasive sensory pollutants that can disrupt wildlife behaviour and reproduction. While most research has focused on diurnal species, the effects of these pollutants on the ecological response of nocturnal predators remain poorly understood. Using data from nine European countries, we investigated the effects of traffic noise, ALAN, and road proximity on nestbox occupancy and reproduction in the Tawny Owl (Strix aluco), a nocturnal raptor widespread across Europe. Traffic noise consistently reduced both nestbox occupancy and reproductive success regardless of road proximity. ALAN also impaired occupancy and reproduction, but its negative effect on reproduction changed based on the proximity to roads. Interestingly, the negative effect of ALAN was stronger in sites further from roads, but it attenuated in their proximity, where owls' hatching success and brood size moderately improved. This finding suggests that near roads, where prey abundance and availability are also generally high, owls may either find the prey regardless of ALAN or they may exploit it to facilitate hunting and brood provisioning. However, vicinity to roads might enhance mortality by vehicle collisions, which represents one of the greatest threats for the conservation of owls. Our findings highlight that anthropogenic noise and the co-occurrence between ALAN and roads can affect settlement decisions and breeding performance in nocturnal raptors, with potential consequences across the food chain. Mitigating anthropogenic noise and promoting nighttime-lighting systems that minimize owls' presence close to roads will represent valuable actions to improve their conservation.
Keywords: ALAN; Anthropogenic noise; Owls; Raptor conservation; Reproductive fitness; Roadside habitats